2013
DOI: 10.1542/peds.2012-1957
|View full text |Cite
|
Sign up to set email alerts
|

Parental Explicit Heuristics in Decision-making for Children With Life-threatening Illnesses

Abstract: Explicit heuristics played an important role in decision-making and communication about decision-making in our population of parents. Recognizing explicit heuristics in parent interactions and understanding their content and functions can aid clinicians in their efforts to partner with parents in the decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…This may contribute to the lengthy decision process we observed, given that using more explicit heuristics, such as fitting unfamiliar decisions into familiar patterns or using “rules of thumb”, may lead to more efficient parental decision making. (38)…”
Section: Discussionmentioning
confidence: 99%
“…This may contribute to the lengthy decision process we observed, given that using more explicit heuristics, such as fitting unfamiliar decisions into familiar patterns or using “rules of thumb”, may lead to more efficient parental decision making. (38)…”
Section: Discussionmentioning
confidence: 99%
“…14 More specifically, what individuals believe they need to do to be a loving or good parent might shape how they view their duties to their child and how they aim to conduct themselves. 1517 In a qualitative study 18 of parents of children with incurable cancer, the parents reported in interviews that, in their view, a good parent remains at the child’s side, shows the child that she or he is cherished, makes unselfish decisions in the child’s best interest, and advocates for the child with the facility’s staff.…”
mentioning
confidence: 99%
“…Parents making these decisions are often presented with complex information in the midst of complicated contexts. Parents are asked to make decisions that are value laden on their child's behalf when the child may be too young, too ill or cognitively unable to be actively involved in decision‐making or to make their wishes known in the present or ever . Parents need understandable information and may benefit from values clarification, both of which are targeted by DAs.…”
Section: Objectivesmentioning
confidence: 99%